Youth in Tanzania's urbanizing mining settlements: Prospecting a mineralized future - Deborah Fahy Bryceson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Over the last fifteen years many African countries have experienced a mining take-off. Mining activities have bifurcated into two sectors: large-scale, capital-intensive production generating the bulk of the exported minerals, and small-scale, labour-intensive artisanal mining, which, at present, is catalyzing far greater immediate primary, secondary and tertiary employment opportunities for unskilled African labourers. Youth residing in mining settlements, have a large vested interest in the current and future development of mining. Focusing on Tanzania as typical of the emerging new mineralizing Africa, this paper, examines youth's role in mining based on recent fieldwork in the country's northwestern gold fields. Youth's current involvement in mining as full-fledged, as opposed to part-time, miners is distinguished. The attitudes of secondary school students towards mining as a form of employment and its impact on economic and social life in mining communities are discussed within the context of the uneasy transitions from an agrarian to a mining-based country, from rural to urban lifestyles, and the growing scope and power of foreign-directed, capital-intensive, corporate mining relative to local labour-intensive artisanal mining.
Keywords: O17; O18; Q33; R23; 330; Africa; artisanal mining; education; employment; generational change; gold